Determinants of Employee Performance in Healthcare Organization: The Role of Work Environment, Workload, and Motivation - Wulandari, Alyaa Ayu Nur; Dara, Siti Ruhana (Human Capital and Organizations, 2023)
This study aims to determine the impact of work environment, workload, and work motivation on employee performance. The study focused on employees working at a hospital in Jakarta, and data was collected through a voluntary questionnaire from 112 respondents. The analytical method used was multiple linear regression, and hypothesis testing revealed that work environment, workload, and work motivation have a combined effect on healthcare employee performance. This study provides valuable insights for decision-makers in healthcare systems, health organizations, and government agencies to enhance the quality and efficiency of health services. It also highlights the importance of maintaining a favorable work environment, including the physical environment and workload, for employee well-being.